Anti-scouring EPDM (Ethylene-Propylene-Diene Monomer) thermal insulation material with good adhesive property and preparation method thereof
By optimizing the component formulation and multi-stage mixing process, a three-dimensional flexible carbonized layer is formed, which solves the problems of insufficient adhesion and erosion resistance of EPDM insulation materials, and achieves high-strength interfacial adhesion and good erosion resistance of the material.
Patent Information
- Application Number
- CN202511504226.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-21
- Publication Date
- 2025-11-18
- Estimated Expiration
- 2045-10-21
AI Technical Summary
The existing EPDM insulation material has weak adhesion properties, resulting in insufficient bonding strength with metals, composite materials and propellants, which easily leads to debonding, causing uneven temperature field inside the engine and loss of control. Furthermore, existing improvement methods have problems with process complexity and material mechanical property degradation.
By optimizing the component formulation, using a combination of organic and inorganic flame retardants, and combining a multi-stage mixing process, adding charring promoters and fiber blends, a three-dimensional flexible carbonized layer is formed, improving the interfacial adhesion and mechanical properties of the material.
It improves the interfacial bonding strength of the material, enhances its erosion resistance, reduces Mooney viscosity, improves the overall performance of the material, avoids problems such as small molecule precipitation and uneven internal structure, and forms a high-temperature resistant protective layer.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of aerospace thermal protection materials, and particularly relates to a kind of anti-washing ternary ethylene-propylene heat insulation material with good bonding performance and a preparation method thereof. BACKGROUND
[0002] The ternary ethylene-propylene heat insulation material is mainly applied to the solid rocket engine cylinder section and the head part, and is used for thermal protection of the inner wall of the engine shell and the propellant washing part, so that the solid rocket engine can be reliably operated in the running process without high-temperature ablation and high-pressure airflow and dense particle erosion, and the performance of the heat insulation material in resisting high-temperature ablation and particle erosion is the current research focus.
[0003] However, the polarity of the ternary ethylene-propylene heat insulation material is weak, and the bonding interface with metals, composite materials, propellants and the like is weak. Once debonding occurs, it will lead to uneven temperature field in the engine, running out of control, material burning through and the like, and cause a catastrophic accident. Therefore, how to improve the bonding strength and reliability of the heat insulation material and various interfaces is also a focus of attention.
[0004] In the existing literature reports, researchers start from increasing the content of ablation-resistant fillers, compounding organic fibers with inorganic fibers, compounding inorganic flame retardants and the like to improve the ablation resistance of the heat insulation material, or add carbon nanotubes to the material to form a good ablation carbonization layer in the ablation process by using the principle of carbon deposition to improve the erosion resistance of the material, and optimize the interface bonding of the heat insulation material by interface treatment, base glue modification (such as introducing acrylate to improve the interface polarity of the material), filler or fiber surface modification and the like. However, these methods increase the Mooney viscosity of the material and the process complexity, deteriorate the mechanical properties of the material, and do not form an effective synergistic effect of the raw materials.
[0005] Chinese patent CN201911274442.4 discloses a modified carbon nanotube reinforced ternary ethylene-propylene rubber heat insulation material and a preparation method. A protective layer is formed on the outside of the carbon nanotube by gas phase deposition pretreatment, thereby reducing the thermal conductivity of the carbon nanotube, the thermal conductivity of the generated carbonization layer and the carbonization ablation rate of the material. However, no measures are taken to improve the overall synergistic coupling of the material, and the carbonization ablation rate is still relatively high (0.166 mm / s) and the Mooney viscosity is high.
[0006] In order to solve the defects existing in the prior art, the present patent application is proposed. SUMMARY
[0007] The present application aims to overcome the defects of the prior art, and provides an anti-erosion EPDM heat-insulating material with good bonding performance and a preparation method thereof.
[0008] The present application provides the following technical solutions: The present application provides an anti-erosion EPDM heat-insulating material with good bonding performance, comprising the following components by weight: 100 parts of EPDM, 15-40 parts of reinforcing filler, 5-15 parts of organic fiber, 5-10 parts of inorganic fiber, 2-5 parts of organic flame retardant, 3-10 parts of inorganic flame retardant, 1-5 parts of carbon-forming component, 5-10 parts of plasticizer, 1-5 parts of activator, 0.02-0.5 parts of carbon-forming promoter, 1-5 parts of promoter, and 1-5 parts of vulcanizing agent.
[0009] The present application solves the technical problem of poor fusion of inorganic flame retardant and EPDM by adding organic flame retardant. The organic flame retardant and the inorganic flame retardant are well fused with the base rubber, and are not easy to precipitate. By controlling the reasonable proportion of each component in the formula, the material achieves good fusion and crosslinking, realizes the coupling between each component, and promotes the formation of synergistic effect between each component in the ablation process. Through the combination of the formula, a three-dimensional flexible carbonized layer and a well-fused primary layer are formed, which solves the problems of incomplete crosslinking, small molecule precipitation, internal structure inhomogeneity, stress, etc., improves the interlayer bonding force, and improves the interfacial adhesion strength. By adding the carbon-forming promoter, the carbon forms structures such as graphene, carbon nanowire, and silicon carbide whisker, and the short fibers and long fibers are compounded, which improves the strength of the ablation carbonized layer and the fusion between the carbonized layer and the base rubber.
[0010] Further, in the above material, the reinforcing filler is one or a combination of two or more of fumed silica, precipitated silica, activated carbon black, calcium carbonate, talc, and clay.
[0011] Further, in the above material, the organic fiber is one or a combination of two or more of aramid fiber, polyphenylene sulfide fiber, phenolic fiber, carbon fiber, and polyimide fiber; and the inorganic fiber is one or a combination of two or more of quartz fiber, aluminum silicate fiber, basalt fiber, mullite fiber, and silicon carbide fiber.
[0012] Further, the organic fiber includes three sizes of 0.1-0.5mm, 0.5-1mm, and 1-3mm, wherein the organic fiber of 0.1-0.5mm is 2-5 parts, the organic fiber of 0.5-1mm is 2-5 parts, and the organic fiber of 1-3mm is 1-5 parts; the inorganic fiber includes three sizes of 0.1-0.5mm, 0.5-1mm, and 1-3mm, wherein the inorganic fiber of 0.1-0.5mm is 1-2 parts, the inorganic fiber of 0.5-1mm is 3-5 parts, and the inorganic fiber of 1-3mm is 1-3 parts.
[0013] Further, in the above material, the organic flame retardant is one or more than two combinations of ammonium polyphosphate, decabromodiphenyl ether, hexachlorotriphosphazene, and phosphate ester; the inorganic flame retardant is one or more than two combinations of aluminum hydroxide, magnesium hydroxide, zinc borate, barium sulfate, and antimony trioxide.
[0014] Further, in the above material, the carbon-forming component is one or more than two combinations of carbon fiber, carbon nanotube, silicon carbide, and graphene.
[0015] Further, in the above material, the plasticizer is one or more than two combinations of liquid paraffin, dioctyl phthalate, aromatic hydrocarbon oil, and naphthenic oil.
[0016] Further, in the above material, the activator is one or more than two combinations of calcium oxide, zinc oxide, magnesium oxide, stearic acid, zinc stearate, triethanolamine, and polyethylene glycol.
[0017] Further, in the above material, the carbon-forming accelerator is one or more than two combinations of tin oxide, nickel oxide, lanthanum oxide, tungsten oxide, and molybdenum oxide.
[0018] Further, in the above material, the vulcanization accelerator is one or more than two combinations of caprolactam disulfide, zinc dibenzyl dithiocarbamate, and tetrabenzyl thiuram disulfide.
[0019] Further, in the above material, the vulcanizing agent is one or more than two combinations of sulfur, dicumyl peroxide, and bis(tert-butyl peroxyisopropyl) benzene.
[0020] The application also provides a preparation method of the above anti-scouring EPDM heat insulation material with good bonding performance, comprising the following steps: S1, melt all the fibers with 10-30 parts of EPDM rubber to form a masterbatch; S2, the masterbatch is put into the internal mixer, and after being scattered, the remaining EPDM rubber is added and uniformly mixed, a small amount of reinforcing filler, organic and inorganic flame retardant, carbon forming component, activator and carbon forming accelerator are added in multiple times, the EPDM rubber is fully dispersed with the reinforcing filler, organic and inorganic flame retardant, carbon forming component, activator and carbon forming accelerator, the water cooling system of the internal mixer is closed to rapidly heat the chamber, so that the rubber is quickly formed into a lump, then the water cooling system is opened, the chamber is kept at a slow temperature rise, the rubber is fully stirred and uniformly mixed, the rubber is discharged, and is cooled to room temperature; S3, the material treated in step S2 is put into the internal mixer, and after being scattered into a flocculent state, the vulcanization accelerator and vulcanization agent are added and uniformly mixed in a dispersed state, the rubber slowly forms a lump as the temperature of the chamber rises, and the plasticizer is added after 1-3 minutes of mixing, so that the rubber is again scattered into a flocculent state and fully dispersed and uniformly mixed, at this time, the water cooling system is closed to rapidly heat the chamber, so that the rubber is quickly formed into a lump, then the water cooling system is opened again, the chamber is kept at a slow temperature rise, the rubber is fully stirred and uniformly mixed, the rubber is discharged, and is cooled to room temperature, thereby obtaining the EPDM heat insulation material.
[0021] The present scheme adopts a multi-stage mixing method, and the materials are added in the order of base rubber→ fiber and base rubber fusion material→ powder filler→ liquid plasticizer, and are mixed dry first and then fused, so that the uniform distribution of each component in the base rubber is improved.
[0022] The present scheme can fully play the function of improving ablation by using a small amount of carbon forming component by reducing the amount of carbon forming component and adding a carbon forming accelerator that can accelerate the deposition of carbon to form a dense carbonized layer; the mixing uniformity of the rubber and the filler is better, the heating flow is good, and the Mooney viscosity of the material is reduced by combining the mixing process optimization measures; the fibers and carbon nanotubes are more uniformly dispersed in the base rubber by fiber premixing and mixing process parameter optimization, and the mechanical property degradation problem caused by uneven stress is eliminated; the present scheme does not need to perform surface modification treatment on the carbon nanotubes, and only by optimizing the types, amount and mixing process of the fillers to improve the micro-interface of the material, the raw materials are uniformly distributed and effectively cooperated, and the complexity of the process is reduced.
[0023] The present application has the following beneficial effects: 1. The application can effectively improve the bonding performance, ablation resistance and erosion resistance of the thermal insulation material, solve the problem of poor process performance of the current erosion-resistant thermal insulation material, form a three-dimensional flexible carbonized layer and a well-fused primary substance layer through reasonable formula combination, solve the problems of incomplete crosslinking, small molecule release, internal structure unevenness and stress, improve the interlayer bonding force and the interface bonding strength, realize the dynamic formation of a protective layer during the ablation process by adding a carbonization promoter, and the protective layer is resistant to high temperature and temperature impact, and forms good bonding between the primary substance layer; the nucleation pinning effect of short fiber pulp during pyrolysis is used to improve the strength and density of the carbonized layer, and the combination of long and short fibers is used to form a flexible and three-dimensional carbonized layer structure. 2. The application can improve the problems of mechanical property decline, ablation rate increase and ablation carbonized layer bulging caused by moisture absorption of inorganic flame retardants, and improve the fusion of the base glue, improve the molding process performance, and avoid precipitation. 3. The preparation process of the application can make each component uniformly dispersed in the base glue, synergistically with material design, and the prepared thermal insulation material has excellent comprehensive performance. BRIEF DESCRIPTION OF DRAWINGS
[0024] In order to more clearly illustrate the technical solutions in the embodiments of the application or the prior art, the drawings needed in the following embodiment or prior art description will be briefly introduced. Obviously, the drawings in the following description are only some embodiments of the application, and other drawings can be obtained by those skilled in the art without creative labor.
[0025] Figure 1 The carbonized layer appearance diagram of the sample prepared by the application example 1 and the comparative example 1, the comparative example 2 after oxygen-ethyne ablation; Figure 2 The SEM diagram of the carbonized layer of the sample prepared by the application example 1; Figure 3 The SEM diagram of the carbonized layer of the sample prepared by the application comparative example 1; Figure 4 The SEM diagram of the carbonized layer of the sample prepared by the application comparative example 2; Figure 5 The SEM diagram of the carbonized layer of the sample prepared by the application comparative example 3; Figure 6 The appearance diagram of the vulcanized sheet of the sample prepared by the application example 1 and the comparative example 3; Figure 7 The fiber distribution of the green sheet prepared by the application example 1 and the comparative example 4 before adding carbon nanotubes; Figure 8Schematic diagram of raw rubber structure before vulcanization (left) and schematic diagram of original layer of thermal insulation material after vulcanization (right) of the present application; Figure 9 Fiber distribution and morphology between original layer and carbonized layer of the sample after ablation of Example 1 of the present application; Figure 10 Morphology of three-dimensional flexible carbonized layer formed after ablation of the sample of Example 1 of the present application; Figure 11 Morphology of carbonized layer after ablation of the sample of Example 1 of the present application; Figure 12 Schematic diagram of raw and cooked material sheet adhesion pull-off test piece of the present application; Figure 13 Adhesion test diagram (left) and device schematic diagram (right) of carbonized layer and original layer of the present application; Figure 14 Carbonized layer damage test diagram (left) and device schematic diagram (right) of the present application. DETAILED DESCRIPTION
[0026] The technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor are within the scope of protection of the present application.
[0027] Example 1 The raw materials are weighed: 100 parts of ternary ethylene-propylene rubber, 15 parts of white carbon black, 5 parts of aramid fiber (1 part of 0.1-0.5 mm fiber, 3 parts of 0.5-1 mm fiber, and 1 part of 1-3 mm fiber), 5 parts of quartz fiber (1 part of 0.1-0.5 mm fiber, 3 parts of 0.5-1 mm fiber, and 1 part of 1-3 mm fiber), 4 parts of ammonium polyphosphate, 3 parts of aluminum hydroxide, 1 part of carbon nanotube, 5 parts of liquid paraffin, 1 part of calcium oxide, 0.02 parts of tin oxide, 1 part of dithiohexanolactam, and 1 part of sulfur.
[0028] The specific preparation method steps are as follows: S1, melt the fibers with 15 parts of base rubber (ternary ethylene-propylene rubber) to make a masterbatch; S2, put the masterbatch into the internal mixer, mix well after dispersing, add the remaining base rubber, and add the powder (reinforcing filler, organic and inorganic flame retardant, carbon forming component, activator, and carbon forming promoter) in three times, stir the base rubber and powder in a dispersed state for 1 min, turn off the water cooling system of the internal mixer, quickly heat the chamber to 50℃, then turn on the water cooling system (constant temperature 20℃), keep the chamber slowly heated, fully stir the rubber mass until uniform, and cool to room temperature at 110℃. S3, the material obtained by step S2 is put into the internal mixer, and after being scattered into flocculation, accelerant and vulcanizing agent are added, so that the material is stirred in a dispersed state for 1 min, then the chamber temperature is raised to 50 DEG C, the rubber mass is formed into a group, liquid paraffin is added after 1 min of mixing, the rubber mass is scattered into flocculation again, and is stirred for 1 min, the water cooling system is closed, the chamber is rapidly heated to 50 DEG C, the rubber mass is formed into a group, the water cooling system is opened again (constant temperature 20 DEG C), the chamber is kept to slowly heat, the rubber mass is fully stirred and uniform, and the chamber temperature is to 80 DEG C for rubbering, the sheet is taken out, and is cooled to room temperature, thereby obtaining the EPDM heat insulation material.
[0029] Example 2 The raw materials are weighed: 100 parts of EPDM, 40 parts of talcum powder, 15 parts of polyphenylene sulfide fiber (5 parts of 0.1-0.5 mm fiber, 5 parts of 0.5-1 mm fiber, and 5 parts of 1-3 mm fiber), 10 parts of mullite fiber (2 parts of 0.1-0.5 mm fiber, 5 parts of 0.5-1 mm fiber, and 3 parts of 1-3 mm fiber), 5 parts of decabromodiphenyl ether, 5 parts of magnesium hydroxide, 5 parts of graphene, 10 parts of aromatic oil, 5 parts of zinc oxide, 0.5 parts of lanthanum oxide, 5 parts of zinc dibenzyl dithiocarbamate, and 5 parts of dicumyl peroxide.
[0030] The specific preparation method steps are as follows: S1, the fibers are fused with 30 parts of base rubber (EPDM) to form a masterbatch; S2, the masterbatch is put into the internal mixer, and after being scattered, the remaining base rubber is uniformly mixed, and the powder is added in 5 times, so that the base rubber and the powder are stirred in a scattered state for 3 min, then the water cooling system of the internal mixer is closed, the chamber is rapidly heated to 55 DEG C, then the water cooling system is opened (constant temperature 25 DEG C), the chamber is kept to slowly heat, the rubber mass is fully stirred and uniform, and the chamber temperature is to 115 DEG C for rubbering, and is cooled to room temperature; S3, the material obtained by step S2 is put into the internal mixer, and after being scattered into flocculation, accelerant and vulcanizing agent are added, so that the material is stirred in a dispersed state for 1 min, then the chamber temperature is raised to 50 DEG C, the rubber mass is formed into a group, liquid paraffin is added after 1 min of mixing, the rubber mass is scattered into flocculation again, and is stirred for 1 min, the water cooling system is closed, the chamber is rapidly heated to 50 DEG C, the rubber mass is formed into a group, the water cooling system is opened again (constant temperature 20 DEG C), the chamber is kept to slowly heat, the rubber mass is fully stirred and uniform, and the chamber temperature is to 80 DEG C for rubbering, the sheet is taken out, and is cooled to room temperature, thereby obtaining the EPDM heat insulation material.
[0031] Example 3 Take the raw materials: 100 parts of ethylene propylene rubber, 25 parts of talcum powder, 10 parts of polyimide fiber (2 parts of 0.1-0.5 mm fiber, 4 parts of 0.5-1 mm fiber, and 4 parts of 1-3 mm fiber), 5 parts of mullite fiber (1 part of 0.1-0.5 mm fiber, 3 parts of 0.5-1 mm fiber, and 1 part of 1-3 mm fiber), 5 parts of decabromodiphenyl ether, 3 parts of magnesium hydroxide, 3 parts of graphene, 7 parts of aromatic hydrocarbon oil, 3 parts of zinc oxide, 0.3 parts of lanthanum oxide, 3 parts of zinc dibenzyl dithiocarbamate, and 3 parts of dicumyl peroxide.
[0032] The specific preparation method steps are: S1, fuse the fibers with 20 parts of base rubber (ethylene propylene rubber) to make a masterbatch; S2, put the masterbatch into the internal mixer, mix the remaining base rubber after dispersing, add the powder in 4 times, stir the base rubber and powder in the dispersed state for 2 minutes, close the water cooling system of the internal mixer, quickly raise the temperature in the chamber to 50°C, then open the water cooling system (constant temperature 20°C), keep the chamber slowly heated, fully stir the rubber particles to uniform, the chamber temperature is 110°C, the rubber is vulcanized, and it is cooled to room temperature; S3, put the material obtained by step S2 into the internal mixer, disperse into flocculation after dispersing, add the accelerator and vulcanizing agent, stir in the dispersed state for 1.5 minutes, then raise the temperature in the chamber to 50°C, the rubber is formed into a group, mix for 1 minute, then add liquid paraffin, disperse the rubber particles into flocculation again, stir for 1.5 minutes, close the water cooling system, quickly raise the temperature in the chamber to 50°C, the rubber is formed into a group, then open the water cooling system again (constant temperature 20°C), keep the chamber slowly heated, fully stir the rubber particles to uniform, the chamber temperature is 80°C, the rubber is vulcanized, and it is cooled to room temperature, then the ethylene propylene rubber heat insulation material is obtained.
[0033] Comparative Example 1 Only the carbon-forming accelerator is not added, and the mass of other raw materials and the process steps are the same as those of Example 1.
[0034] Comparative Example 2 Only the length and size of the fiber are not set (the size of aramid fiber and quartz fiber is 0.1-0.5 mm), and the mass of other raw materials and the process steps are the same as those of Example 1.
[0035] Comparative Example 3 Only the combination of organic and inorganic flame retardants is not set (only aluminum hydroxide is added), and the mass of other raw materials and the process steps are the same as those of Example 1.
[0036] Comparative Example 4 The raw material ratio is the same as that of Example 1, and the multi-stage mixing process is not used, and the specific preparation method steps are: S1, fuse the fibers with 15 parts of base rubber to make a masterbatch; S2, put the masterbatch and the remaining base rubber into the internal mixer, stir for 5 min, add the powder, stir for 5 min, fully stir the rubber mass to be uniform, vulcanize at a chamber temperature of 110-115℃, and air to room temperature; S3, put the material obtained in step S2 into the internal mixer, stir for 3 min, add the accelerator and vulcanizing agent, stir for 2 min, add liquid paraffin, stir for 5 min, vulcanize at a chamber temperature of 80-85℃, sheet out, and air to room temperature to obtain the ternary EPDM heat insulation material.
[0037] The materials prepared in Examples 1-3 and Comparative Examples 1-4 were subjected to performance tests (tensile strength, elongation at break, oxygen-ethyne line ablation rate, green-cured adhesion peel strength, Mooney viscosity, carbonized layer and original layer adhesion, and carbonized layer damage). The results are shown in Table 1. The higher the tensile strength and elongation at break, the better the mechanical properties of the material; the lower the oxygen-ethyne line ablation rate, the better the ablation resistance of the material; the greater the green-cured adhesion peel strength, the better the adhesion properties of the material; the lower the Mooney viscosity, the better the flowability and processability of the material; the higher the carbonized layer and original layer adhesion and the greater the carbonized layer damage, the better the resistance of the carbon layer formed after ablation to erosion.
[0038] Table 1. Performance results of the materials prepared in Examples 1-3 and Comparative Examples 1-4 Test standard Example 1 Example 2 Example 3 Comparative example 1 Comparative example 2 Comparative example 3 Comparative example 4 Mn l (1 + 4) GB / T 1232 56 65 60 57 65 58 67 Tensile strength / MPa GB / T 528-2009 8.0 10.5 9.0 7.5 8.5 8.6 8.0 Elongation at break / % GB / T 528-2009 380% 300% 350% 400% 360% 290% 280% Green and cured adhesive peel strength / MPa QJ 2038.1A-2004 3.5 3.8 3.6 3.2 2.3 2.1 2.5 Oxyacetylene line ablation rate / mm / s GJB 323A-1996 0.045 0.021 0.035 0.060 0.055 0.070 0.060 Adhesion of carbonized layer to original substrate / N / 22 28 26 20 18 15 12 Carbonized layer failure force / N / 80 90 85 60 75 70 58 As can be seen from Table 1, compared with Example 1, the Mooney viscosity and mechanical properties of the sample without carbonization promoter (Comparative Example 1) changed little, the green-cured peel strength decreased slightly, but the line ablation rate increased significantly, and the carbonized layer and original layer adhesion and damage both decreased, and the carbonized layer's resistance to erosion deteriorated. This shows that the carbonization promoter significantly affects the ablation resistance and erosion resistance of the material.
[0039] Compared with Example 1, the Mooney viscosity of the sample without fiber compounding (Comparative Example 2) increased significantly, the mechanical properties changed little, the green-cured peel strength decreased, the carbonized layer and original layer adhesion and damage both decreased, and the carbonized layer's resistance to erosion deteriorated. This shows that fiber compounding significantly affects the Mooney viscosity, adhesion properties, and erosion resistance of the material.
[0040] Compared with Example 1, the Mooney viscosity of the sample without flame retardant compounding (Comparative Example 3) changed little, the elongation at break decreased significantly, the green-cured peel strength decreased, the carbonized layer and original layer adhesion and damage both decreased, and the carbonized layer's resistance to erosion deteriorated. This shows that flame retardant compounding significantly affects the Mooney viscosity, adhesion properties, and erosion resistance of the material.
[0041] Compared with Example 1, the Mooney viscosity of the sample without segmented mixing process (Comparative Example 4) is obviously increased, the elongation at break is significantly reduced, the green and cured peel strength is reduced, the adhesion and breaking force of the carbonized layer to the original layer are reduced, and the erosion resistance of the carbonized layer is deteriorated. This shows that the segmented mixing process significantly affects the Mooney viscosity, mechanical properties, bonding properties and erosion resistance of the material.
[0042] Compared with Example 1, the fiber content and type, the flame retardant content and type, and the vulcanization system of Examples 2 and 3 are different, so the mechanical properties, Mooney viscosity, bonding properties, and erosion resistance to ablation have some fluctuations, but the comprehensive performance is better than that of the comparative sample.
[0043] The present application requires that the Mooney viscosity of the material is ≤65, the tensile strength is ≥7.5 MPa, the elongation at break is ≥300%, the green and cured peel strength is ≥3.0 MPa, the oxyacetylene line ablation rate is ≤0.05 mm / s, the adhesion of the carbonized layer to the original layer is ≥20 N, and the breaking force of the carbonized layer is ≥80 N. It can be considered that the comprehensive performance is good.
[0044] Referring to Figure 1 , the carbonized layer of the sample of Example 1 is complete and not easy to be damaged, the carbonized layer of the sample of Comparative Example 1 (without adding carbon promoter) is easy to be damaged, and the carbonized layer of the sample of Comparative Example 2 (without matching the size of the fiber) is easy to be layered; Referring to Figure 2 , it can be seen that the sample prepared in Example 1 forms a dense, three-dimensional carbonized layer structure with multiple size fibers; referring to Figure 3 , it can be seen that the sample without adding carbon promoter only forms a relatively loose carbonized layer structure; referring to Figure 4 , it can be seen that the sample without matching the size of the fiber does not form a good three-dimensional carbonized layer structure; referring to Figure 5 , it can be seen that the sample without matching the flame retardant does not form a good three-dimensional carbonized layer structure; Figure 6 The appearance of the vulcanized sheet of the sample prepared in Example 1 and Comparative Example 3 of the present application is shown in the figure. It can be seen that the sample without matching the flame retardant has more precipitates, indicating that the internal filler compatibility is poor; Figure 7 The fiber distribution of the green sheet before adding carbon nanotubes (for convenience, the fiber dispersion of the sheet is observed) of Example 1 and Comparative Example 4 of the present application is shown in the figure. It can be seen that the internal fiber distribution of the sample without segmented mixing process is uneven, and there is more fiber aggregation phenomenon.
[0045] Figure 8 The structure diagram of the green rubber before vulcanization (left) and the schematic diagram of the original layer of the thermal insulation material after vulcanization (right) of the present application are shown in the figure. It can be seen that through the combination, matching and multi-stage mixing process of the components, the components are uniformly dispersed and well integrated in the material, and the crosslinking point distribution after vulcanization is more uniform.
[0046] Figure 9 The fiber distribution and morphology between the original layer and the carbonized layer after ablation of the sample of the present application, Figure 10 The fiber morphology after ablation of the sample of the present application, Figure 11 The carbonized layer morphology after ablation of the sample of the present application. As can be seen from the figure, by adding compounded organic and inorganic fibers, multi-scale fibers are formed in the mixing process, and a three-dimensional network structure is formed by interweaving in the thermal insulation material. During the ablation process, part of the fibers pyrolyze and carbonize, and are pinned in the carbonized layer, and part of the fibers are not carbonized, but are combined with the original layer, thereby forming a three-dimensional flexible carbonized structure; at the same time, under the condition of high temperature ablation, the carbon-forming components in the material rapidly form a dense carbonized layer under the action of the compounded flame retardant and carbon-forming promoter, filling the large pores formed in the carbonization and pyrolysis process of the thermal insulation material; the above two processes synergistically promote the formation of a three-dimensional flexible network carbonized layer.
[0047] Figure 12-14 The adhesion between the carbonized layer and the original layer and the carbonized layer failure test method in Table 1 are shown in the schematic diagram, Figure 12 The green and cooked material sheet bonding and tearing test piece of the present application is shown in the schematic diagram, Figure 13 The carbonized layer and the original layer adhesion test diagram (left) and device schematic diagram (right) of the present application are shown, Figure 14 The carbonized layer failure test diagram (left) and device schematic diagram (right) of the present application are shown.
[0048] In summary, the present application can effectively improve the bonding performance, ablation resistance and erosion resistance of the thermal insulation material, solve the problem of poor process performance of the current erosion-resistant thermal insulation material; through reasonable formula combination, a three-dimensional flexible carbonized layer and a well-fused original layer can be formed, solving the problems of incomplete crosslinking, small molecule emission, internal structure unevenness, stress, etc., improving the interlayer bonding force and the interface bonding strength; by adding a carbon-forming promoter, a protective layer is dynamically formed during the ablation process, and the protective layer is resistant to high temperature and temperature shock, and changes gradually, forming a good combination with the original layer; by using the nucleation pinning effect of short fiber pulp during thermal cracking, the strength and density of the carbonized layer are improved, and by using the compounding of long and short fibers, a flexible and three-dimensional carbonized layer structure is formed.
[0049] The above only describes the preferred embodiments of the present application and is not intended to limit the present application, and any modification, equivalent replacement, improvement, etc. made within the spirit and principles of the present application shall be included in the protection scope of the present application.
Claims
1. An erosion-resistant EPDM insulation material with good adhesion properties, characterized in that, It includes the following components by weight: 100 parts EPDM rubber, 15-40 parts reinforcing filler, 5-15 parts organic fiber, 5-10 parts inorganic fiber, 2-5 parts organic flame retardant, 3-10 parts inorganic flame retardant, 1-5 parts charring component, 5-10 parts plasticizer, 1-5 parts activator, 0.02-0.5 parts charring accelerator, 1-5 parts vulcanization accelerator, and 1-5 parts vulcanizing agent.
2. The erosion-resistant EPDM insulation material with good adhesion properties as described in claim 1, characterized in that: The reinforcing filler is one or more of the following: fumed silica, precipitated silica, activated carbon black, calcium carbonate, talc, and clay.
3. The erosion-resistant EPDM insulation material with good adhesion as described in claim 1, characterized in that: The organic fiber is one or more of aramid fiber, polyphenylene sulfide fiber, phenolic fiber, carbon fiber, and polyimide fiber; the inorganic fiber is one or more of quartz fiber, aluminum silicate fiber, basalt fiber, mullite fiber, and silicon carbide fiber.
4. The erosion-resistant EPDM insulation material with good adhesion as described in claim 1, characterized in that: The organic fibers include organic fibers of three sizes: 0.1-0.5 mm, 0.5-1 mm, and 1-3 mm, wherein the organic fibers of 0.1-0.5 mm comprise 2-5 parts, the organic fibers of 0.5-1 mm comprise 2-5 parts, and the organic fibers of 1-3 mm comprise 1-5 parts; the inorganic fibers include inorganic fibers of three sizes: 0.1-0.5 mm, 0.5-1 mm, and 1-3 mm, wherein the inorganic fibers of 0.1-0.5 mm comprise 1-2 parts, the inorganic fibers of 0.5-1 mm comprise 3-5 parts, and the inorganic fibers of 1-3 mm comprise 1-3 parts.
5. The erosion-resistant EPDM insulation material with good adhesion as described in claim 1, characterized in that: The organic flame retardant is one or a combination of two or more of the following: ammonium polyphosphate, decabromodiphenyl ether, hexachlorocyclotriphosphazene, and phosphate esters; the inorganic flame retardant is one or a combination of two or more of the following: aluminum hydroxide, magnesium hydroxide, zinc borate, barium sulfate, and antimony trioxide.
6. The erosion-resistant EPDM insulation material with good adhesion as described in claim 1, characterized in that: The carbon-forming components are one or more of carbon fibers, carbon nanotubes, silicon carbide, and graphene.
7. The erosion-resistant EPDM insulation material with good adhesion as described in claim 1, characterized in that: The carbonization promoter is one or a combination of two or more of tin oxide, nickel oxide, lanthanum oxide, cerium oxide, tungsten oxide, and molybdenum oxide.
8. The erosion-resistant EPDM insulation material with good adhesion as described in claim 1, characterized in that: The plasticizer is one or more of liquid paraffin, dioctyl sebate, aromatic hydrocarbon oil, and cycloalkane oil; the activator is one or more of calcium oxide, zinc oxide, magnesium oxide, stearic acid, zinc stearate, triethanolamine, and polyethylene glycol.
9. The erosion-resistant EPDM insulation material with good adhesion as described in claim 1, characterized in that: The vulcanization accelerator is one or more of dicaprolactam disulfide, zinc dibenzyl dithiocarbamate, and tetrabenzyl thiuram disulfide; the vulcanizing agent is one or more of sulfur, dicumyl peroxide, and bis(tert-butyl peroxide)benzene.
10. A method for preparing the erosion-resistant EPDM insulation material with good adhesion properties according to any one of claims 1 to 9, characterized in that, Includes the following steps: S1. Fuse all fibers with 10-30 parts of EPDM rubber to make a masterbatch; S2. Add the masterbatch to the internal mixer, break it up, add the remaining EPDM rubber and mix well. Add the reinforcing filler, organic and inorganic flame retardants, carbon-forming components, activators, and carbon-forming accelerators in small amounts several times to ensure that the EPDM rubber is fully dispersed with the reinforcing filler, organic and inorganic flame retardants, carbon-forming components, activators, and carbon-forming accelerators. Turn off the water cooling system of the internal mixer to allow the chamber to heat up rapidly and promote the rapid agglomeration of the rubber compound. Then turn on the water cooling system to keep the chamber heating up slowly and stir the rubber agglomerates thoroughly. Discharge the rubber and let it dry to room temperature. S3. The material obtained in step S2 is put into a mixer and broken into flocculent form. Then, accelerator and vulcanizing agent are added to mix it evenly in a dispersed state. As the temperature of the chamber rises, the rubber compound slowly forms clumps. After mixing for 1-3 minutes, plasticizer is added to break the clumps into flocculent form again and disperse them evenly. At this time, the water cooling system is turned off to allow the temperature in the chamber to rise rapidly and promote the rapid clumping of the rubber compound. Then, the water cooling system is turned on again to allow the temperature in the chamber to rise slowly and the clumps to be fully stirred evenly. The rubber is then discharged, sheeted, and dried to room temperature to obtain the EPDM insulation material.
Citation Information
Patent Citations
Modified carbon nanotube-reinforced EPDM rubber thermal insulation material and its preparation method
CN111019243B
Silicone rubber based ablation-resisting heat insulation composite material and preparation method thereof
CN104629374A
Low-density ablation-resistant ethylene propylene diene monomer material and preparation method thereof
CN112812447A
Low-density solid rocket engine heatproof material and preparation method thereof
CN115304918A
Ethylene-propylene-diene monomer rubber with low density, ablation resistance and good mechanical property and preparation method of ethylene-propylene-diene monomer rubber
CN118638365A